2018
DOI: 10.1002/jcb.26628
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐320 promotes B cell proliferation and the production of aberrant glycosylated IgA1 in IgA nephropathy

Abstract: IgA nephropathy (IgAN) is one of the most common primary glomerulonephritis. However, the etiology of this disease is complex and the pathogenesis of IgAN is still unknown. MicroRNAs (miRNAs) play important roles in a lot of pathological and physiological processes. In this study, we showed that the expression of miR-320 was significantly upregulated in renal tissues and urinary of IgAN patients. Moreover, the intra-renal expression level of miR-320 had significant correlation with miR-320 expression in the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…43 Overexpression of hsa-miR-320 promotes B-cell proliferation through suppressing Phosphatase and tensin homolog(PTEN) expression and promotes cyclin D1 expression. 44 Our data also confirmed that high expression of hsa-miR-320d, hsa-miR-320c, and hsa-miR-320b has a negative prognosis and associated with bad response to anti-PD-1 treatment in patients with NSCLC. The observation of downregulated hsa-miR-125b-5p in PR-pre group also supported the role of hsa-miR-125b-5p as a T-cell suppressor in another study.…”
Section: Open Accesssupporting
confidence: 82%
“…43 Overexpression of hsa-miR-320 promotes B-cell proliferation through suppressing Phosphatase and tensin homolog(PTEN) expression and promotes cyclin D1 expression. 44 Our data also confirmed that high expression of hsa-miR-320d, hsa-miR-320c, and hsa-miR-320b has a negative prognosis and associated with bad response to anti-PD-1 treatment in patients with NSCLC. The observation of downregulated hsa-miR-125b-5p in PR-pre group also supported the role of hsa-miR-125b-5p as a T-cell suppressor in another study.…”
Section: Open Accesssupporting
confidence: 82%
“…U6 is highly conserved among species 12 and relatively stable in different tissues and cells from the same organism. U6 is one of the most commonly used miRNA housekeeping genes and is often used in the study of IgAN kidney tissue and renal cell lines 18 , 21 , 22 . Currently, U6 is the most widely using reference gene in urinary sediment miRNAs studies 4 8 , 19 , 23 that are primarily based on studies using tissue samples and cell lines 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In similar experiments, having discovered that upregulated miR-320 expression in the renal tissue and urine of IgAN patients was accompanied by reduced expression of Cosmc, Li et al overexpressed miR-320 in B cells and discovered that this had the effect of downregulating Cosmc expression as well as inducing B cell proliferation [65], again implicating this miR in the regulation of IgA1 O-glycosylation. Potential miR interactions resulting in the galactosylation of IgA are illustrated in Figure 4.…”
Section: B Cellsmentioning
confidence: 97%